Prospective on using fibre mid-infrared supercontinuum laser sources for in vivo spectral discrimination of disease. Issue 24 (26th November 2018) - Seddon, Angela B.; Napier, Bruce; Lindsay, Ian; Lamrini, Samir; Moselund, Peter M.; Stone, Nicholas; Bang, Ole; Farries, Mark
Abstract : Mid-infrared (MIR) fibre-optics may play a future role in in vivo diagnosis of disease, including cancer. Abstract : Mid-infrared (MIR) fibre-optics may play a future role in in vivo diagnosis of disease, including cancer. Recently, we reported for the first time an optical fibre based broadband supercontinuum (SC) laser source spanning 1.3 to 13.4 μm wavelength to cover the spectral 'fingerprint region' of biological tissue. This work has catalysed the new field of fibre MIR-SC and now very bright sources equivalent to a 'few synchrotrons' have been demonstrated in fibre. In addition, we have made record transparency MIR fibre for routeing the MIR light and reported first-time MIR photoluminescence (with long lifetime) in small-core, rare earth ion doped, MIR fibre – an important step towards MIR fibre lasing at >4 μm wavelength for pumping fibre MIR-SC. First time fibre MIR-SC spectroscopic imaging of colon tissue is described at wavelengths in the 'fingerprint region'.